2001
DOI: 10.1007/s00232-001-0098-x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Aldosterone's Action on Epithelial Na + Transport

Abstract: Aldosterone maintains total organism sodium balance in all higher vertebrates. The level of sodium reabsorption is primarily determined by the action of aldosterone on epithelial sodium channels (ENaC) in the distal nephron. Recent work shows that, in an aldosterone-sensitive renal cell line (A6), aldosterone regulates sodium reabsorption by short- and long-term processes. In the short term, aldosterone regulates sodium transport by inducing expression of the small G-protein, K-Ras2A, by stimulating the activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
57
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(57 citation statements)
references
References 0 publications
0
57
0
Order By: Relevance
“…Others conclude that the effect is due exclusively to an increase in channel density (27), and that aldosterone, vasopressin, and insulin act on sodium transport by promoting the incorporation of channels in the apical membrane (28). Conversely, several groups have suggested that aldosterone increases the ENaC open probability (15), possibly by posttranslational modification (26,29). It has been suggested that regulation of trafficking and͞or functioning of sodium channels is controlled by aldosterone-induced modulatory proteins and kinases (30).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Others conclude that the effect is due exclusively to an increase in channel density (27), and that aldosterone, vasopressin, and insulin act on sodium transport by promoting the incorporation of channels in the apical membrane (28). Conversely, several groups have suggested that aldosterone increases the ENaC open probability (15), possibly by posttranslational modification (26,29). It has been suggested that regulation of trafficking and͞or functioning of sodium channels is controlled by aldosterone-induced modulatory proteins and kinases (30).…”
Section: Resultsmentioning
confidence: 99%
“…It has been suggested that regulation of trafficking and͞or functioning of sodium channels is controlled by aldosterone-induced modulatory proteins and kinases (30). One regulatory cascade proposed acts via aldosterone-induced expression of small G protein K-Ras2A, with subsequent activation of PI3K, which produces phosphoinositol-3,4,5-trisphosphate (PIP 3 ) and that this is a direct regulator of ENaC open probability (29). This regulation also involves serum-and glucocorticoid-kinase (SGK1) that prevents ENaC degradation and mitogen-activated protein kinase (MAPK) that in contrast stimulates channel degradation (31,32).…”
Section: Resultsmentioning
confidence: 99%
“…Sodium reabsorption in the aldosterone-sensitive distal nephron (ASDN), 3 which includes the connecting tubule and the cortical collecting duct (CCD), determines final concentration of Na ϩ excreted in urine (3)(4)(5). Activity of the epithelial Na ϩ channel (ENaC) accounts for electrogenic Na ϩ reabsorption at this segment (3,4,6,7). Therefore, ENaC is critical for regulation of sodium balance and circulating volume (4,(7)(8)(9)(10).…”
Section: Whereas Regulation Of Enac By Aldosterone Is Generally Accepmentioning
confidence: 99%
“…ENaC-mediated Na ϩ reabsorption also provides the electrical driving force for K ϩ secretion mediated by the renal outer medullary K ϩ (ROMK) channel and the "big conductance" K ϩ channel (15). ENaC activity in the ASDN is regulated by the renin-angiotensin-aldosterone system (RAAS) in response to variations in dietary Na ϩ intake with aldosterone being the primary ENaC activator (4,6,7). Elevations in circulating aldosterone levels increase ␣-ENaC expression and redistribution of ␤-and ␥-ENaC from cytosol to the apical membrane (16,17).…”
Section: Whereas Regulation Of Enac By Aldosterone Is Generally Accepmentioning
confidence: 99%
“…Aldosterone is a major regulator of epithelial Na ϩ absorption and acts in large part through ENaC induction in the renal collecting duct (3,4). Aldosterone administration or hyperaldosteronism induced by a low-Na ϩ diet increases ENaC␣ gene transcription, without increasing ␤-or ␥-subunit expression (5-9), and without a separate effect on ENaC␣ mRNA turnover (10) in this segment.…”
mentioning
confidence: 99%